Amostragem sequencial para avaliação de lagartas e percevejos em soja - Stefanelo, Lucas da Silva (2017)
Among the principal limitations of grain yield in soybean are the insect pests, especially the defoliating caterpillars and Sucking stink bugs grains. It is necessary to reveal and quantify these insects for proper decision-making according to pre-established control levels. So, for the implementation of appropriate management of these soybean insect pests, there is necessity of establishing a sampling plan that will permit the estimation of the population density of pests, effective, trusty and less time-consuming. This work aims to establish a sequential sampling plan for caterpillars and stink bugs soybean according to the sequential test of probability rates. Data were collected in two growing seasons (2010/2011 and 2012/2013). Were counted the number of small caterpillars (<1.5 cm) and large (> 1.5 cm) species Anticarsia gemmatalis (Hübner, 1818), Chrysodeixis includens (Walker, 1857) and Spodoptera eridania (Cramer, 1872) as well as stink bugs nymphs and adults of the species Piezodorus guildinii (Westwood, 1873), Nezara viridula (Linnaeus, 1758), Euschistus heros (Fabricius, 1794) Dichelops furcatus (Fabricius, 1775), Edessa meditabunda (Fabricius, 1794) and Chinavia sp. (Say, 1831) using the vertical cloth-to-beat in a grid of 154 sample points was marked with a 20 × 20 m spacement in area of 6.16 ha in soybean. The distribution of caterpillars, small and large in soybean is aggregated. According to the sequential sampling plans a sufficient number of sample units for soybean caterpillars assessment is 14. According to the sequential sampling plan sufficient number of samples for the evaluation of adult bugs in soybeans is 17.